CSR reporting practices: The case of University of Bari - Francesco Campobasso; Graziana Galeone; Simona Ranaldo; Matilda Shini (Administrative Sciences, 2022)
Corporate social responsibility (CSR) is a relevant topic for researchers and practitioners, widely explored with reference to companies. However, there are still few studies that address how higher education institutions integrate CSR practices into their strategy. This represents an important limitation since the university, through academic training and research activity, is the main promoter of CSR practices among different categories of stakeholders. Given the many benefits associated with the adoption of CSR, this study aims to explore the topic of CSR in universities, as they are institutions that act in the public interest and represent the ideal context for spreading the culture of preserving environmental and social, as well as economic, sustainability. The main purpose of this study is to explore, through the methodology of case studies, the type and effectiveness of the tools used by universities, specifically the University of Bari, to disseminate and integrate CSR into corporate strategy. Furthermore, this study aims to investigate how the university ensures the involvement of stakeholders, represented in particular by professors, administrators and students (stakeholder approach), in CSR initiatives. The analysis revealed the centrality of the investigated university in promoting CSR issues and sustainable territorial development. Finally, the study provides empirical evidence of the actions and methods of integrating CSR practices into corporate strategy and the ways in which stakeholders are involved.
Keywords: 350; stakeholder engagement; sustainability; universities; corporate social responsibility (CSR); corporate strategy